NON-TRADITIONAL METHODS OF COMMUNICATIVE-ORIENTED TRAINING OF FOREIGN LANGUAGE TEACHERS IN HIGHER EDUCATION INSTITUTIONS OF THE USA (Comparative Professional Pedagogy, 2023)
The article deals with non-traditional methods of communicative-oriented teaching of future foreign language teachers in higher education institutions of the USA aimed at developing the ability to adequately express thoughts in a particular language. The main principle of communicative teaching is language activity. Participants in communication should learn to solve real and conditional tasks of joint activity with the help of a foreign language. In this case, learning takes place through activities, which are realized with the help of methodological techniques and exercises. Examples of non-traditional methods of communication in foreign classes at higher education institutions in the USA include the following types of tasks: communication games; communicative stimulations in role-plays and problem-solving; free communication (socialization). The purpose of communicative tasks is to encourage students to solve new communication problems with the help of language tools learned on the basis of the original polylogues. Particular attention is paid to the three-part form of performing communicative-oriented tasks (three-phase frame-work), which are performed in three stages: preparatory (pre-activity); executive (while-activity); final (post-activity). It is noted that an important role in the implementation of non-traditional methods is played by the informative competence of students, which includes: information "frames"; formed knowledge (schemata); language representation of the world in its foreign language form; background knowledge; general knowledge. It is established that special attention should be paid to communicative skills when using non-traditional methods of communication for future teachers in foreign classes at higher education institutions in the USA. The article analyzes students' communication skills, which are divided into the following blocks: 1. Requirements for learning to speak. Fields of communication and topics (ability to communicate with peers). 2. Dialogic speech (different types of dialogues, questioning, exchange of opinions, information, etc.) 3. Monologue speech (statements, retelling of what has been heard, seen or read, etc.) Each of the three blocks involves the development of certain communication skills. The authors have considered several examples of non-traditional methods of communicative-oriented teaching of future foreign teachers in higher education institutions of the USA, namely: "sketch", "role play", "round table", "discussion".
Keywords: non-traditional methods; communicative-oriented teaching; future foreign language teachers; higher education institutions; methodological techniques; communicative games; the USA